1990
DOI: 10.1007/bf01289348
|View full text |Cite
|
Sign up to set email alerts
|

Near-barrier transfer and fusion of the systems33S +90,91,92Zr

Abstract: Double differential cross sections of all prominent transfer channels have been measured in the systems 338+9~ at two energies close to the nominal Coulomb barrier. In addition the fusion excitation functions of these systems have been measured below and around the barrier. The angular-and Q-distributions of the most important transfer reactions have been analysed in the framework of a simple semiclassical formalism. Particularly the two-nucleon transfer angular distributions exhibit strong multi step coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…enhancements in sub-barrier fusion cross sections). The importance of such systems was demonstrated in the study [7] of 33S+9~ It was observed, in agreement with other studies [8], that the inelastic couplings 1) are responsible for only part of the asymptotic barrier shifts Di in the sub-barrier fusion cross sections, and 2) cannot explain the isotopic effects. Hence coupling to the quasi-elastic transfer channels was needed; the measured transfer cross sections allowed to extract the form factors used in CC calculations which, taking into account both inelastic and transfer channels, gave a rathe~ good description of the D~.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…enhancements in sub-barrier fusion cross sections). The importance of such systems was demonstrated in the study [7] of 33S+9~ It was observed, in agreement with other studies [8], that the inelastic couplings 1) are responsible for only part of the asymptotic barrier shifts Di in the sub-barrier fusion cross sections, and 2) cannot explain the isotopic effects. Hence coupling to the quasi-elastic transfer channels was needed; the measured transfer cross sections allowed to extract the form factors used in CC calculations which, taking into account both inelastic and transfer channels, gave a rathe~ good description of the D~.…”
Section: Introductionsupporting
confidence: 82%
“…In the same work [7], a decrease is reported in the transfer angular distributions at backward angles steeper than the predictions of a semiclassical model, where the absorption probability was derived from the elastic scattering cross sections. The "missing" cross section (Aat) was interpreted as loss of transfer flux feeding more complex channels and/or fusion.…”
Section: Introductionmentioning
confidence: 80%
“…where D is the distance of closest approach and N is another constant, known function of k. For more details about the adopted formulas see also [3].…”
Section: Fusion Cross Sections: Interplay With Transfermentioning
confidence: 99%
“…The set-up for the transfer measurements is described in detail in [3]. The beam-like particles were detected with a TOF--AE--E telescope.…”
Section: Transfer Cross Sections (Experimental)mentioning
confidence: 99%
See 1 more Smart Citation